Knowledge and perception of massive open online courses among medical students of Perambalur district, Tamilnadu, India - Kumar, Rakesh; Rajesh, S.; Kanna, K. Rajesh; Sujin, S. Rohit (International Journal Of Community Medicine And Public Health, 2021)
Background: Coronavirus outbreak has forced a prolonged closure of educational institutes all over world including India which have affected the regular classroom studies and skill acquisition by students. The aim of the study was to assess the knowledge and perception regarding mass open online courses (MOOC) among medical students. Methods: A web-based cross-sectional study using google form survey tool was conducted among undergraduate medical students. Questions were asked on demographic information, use and accessibility of information technologies, awareness and utilization of MOOC and barriers and motivations for course enrollment and completion. Results: Overall 224(54.9%) of medical students had ever heard about MOOC. Out of them, only 31.6% students had actually enrolled for any online course. Further, course completetion rate was only 11.6%. Age and year of study was significantly associated with enrolment to MOOC. Important motivation for enrolment were learning new thing, learning medicine and for better career prospects while common barriers were low internet speed and lack of time. Among those who completed the course, most of them had a satisfactory or very satisfactory level of satisfaction with regard to overall experience, quality of presented material, technology used, and video lectures. Conclusions: There is poor awareness and utilization of MOOC among medical students which can hamper their learning particularly in absence on regular classroom teaching. There is need of blended curriculum harnessing the advantages of MOOC platform which will aid students continue learning in difficult times.